1992
DOI: 10.1111/j.1365-2141.1992.tb06407.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for severe sickle cell anaemia

Abstract: Five children with sickle cell anaemia underwent bone marrow transplantation (BMT) for severe clinical disease. The conditioning regimen for BMT was in busulfan plus cyclophosphamide. The allograft contained more than 5 x 10(8) nucleated cells per kg recipient. Prophylaxis of GVHD consisted of methotrexate and cyclosporin A. Therapy was well tolerated. Duration of neutropenia (less than 0.5 x 10(9)/l) was short (14-25 d). Platelet recovery (greater than 50 x 10(9)/l) occurred between day 12 and 45. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The results of the current study confirm and extend earlier findings of successful HCT for sickle cell disease (Ferster et al, 1992;Vermylen et al, 1993Vermylen et al, , 1998Vermylen & Cornu, 1994;Walters et al, 1996Walters et al, , 1997Walters et al, , 2000Walters et al, , 2001Bernaudin, 1999) With disease-free and overall survival rates of 85% and 97%, respectively, HCT is a suitable treatment option that can be applied with a curative intent when an HLA-matched sibling donor is available. Our observations are supported by the ongoing utilisation of HCT for sickle cell disease by affected families and their physicians after completion of the national clinical trial, even though alternative supportive therapies, such as hydroxycarbamide and chronic red blood cell transfusions, are readily available.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the current study confirm and extend earlier findings of successful HCT for sickle cell disease (Ferster et al, 1992;Vermylen et al, 1993Vermylen et al, , 1998Vermylen & Cornu, 1994;Walters et al, 1996Walters et al, , 1997Walters et al, , 2000Walters et al, , 2001Bernaudin, 1999) With disease-free and overall survival rates of 85% and 97%, respectively, HCT is a suitable treatment option that can be applied with a curative intent when an HLA-matched sibling donor is available. Our observations are supported by the ongoing utilisation of HCT for sickle cell disease by affected families and their physicians after completion of the national clinical trial, even though alternative supportive therapies, such as hydroxycarbamide and chronic red blood cell transfusions, are readily available.…”
Section: Discussionsupporting
confidence: 80%
“…The severity of these complications warrants the institution of therapeutic interventions that prevent and eliminate these life-threatening events. It has been shown previously that haematopoietic stem cell transplantation (HCT) can cure patients with sickle cell disease and is currently the only known cure for this disease (Ferster et al, 1992;Walters et al, 1996;Vermylen et al, 1998;Bernaudin, 1999). However, its toxicity limits broader application.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The last survey of the Belgian experience in BMT for SCD, which included 50 patients, showed an event-free survival of 85% with an overall survival rate of 93%. 13 In patients lacking an HLA-identical sibling, refusing the BMT procedure, too old for BMT, or in whom a contraindication exists, HU is the only drug that has been proven to modify the disease at short or middle term, [6][7][8]14 with acceptable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Her leukemia was cured and she was converted to sickle cell trait [132]. In the following decade, several pilot studies of bone marrow transplantation for the treatment of young patients with symptomatic SCD demonstrated eradication of the underlying disease with low transplantation-related mortality [133][134][135][136]. In 1996, Walters et al reported the results of HLAidentical allogeneic transplantation in 22 individuals with SCD (all <16 years old), of which 20 survived and 16 had stable engraftment of donor cells [137].…”
Section: Hematopoietic Stem Cell Transplantation In Scdmentioning
confidence: 99%